Antibody Course and Memory B-Cell Response in the First Year After Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (1st February 2022) - Kannenberg, Judith; Trawinski, Henning; Henschler, Reinhard; Buhmann, Raymund; Hönemann, Mario; Jassoy, Christian
Abstract: Background: The possibility of repeat infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) raises questions regarding quality and longevity of the virus-induced immune response. Methods: The antibody course and memory B-cell (MBC) response against SARS-CoV-2 proteins, influenza virus nucleoprotein (NP), and tetanus toxin were examined in adults with mild to moderate SARS-CoV-2 infection in the first year after infection. Results: The concentration of SARS-CoV-2 receptor binding domain (RBD)-specific antibodies was low compared with the concentration of influenza virus NP-specific antibodies. The SARS-CoV-2 RBD antibody half-life increased from 95 days in the first 6 months to 781 days after 9–12 months. The SARS-CoV-2 NP antibody half-life increased from 88 to 248 days. Two thirds of the subjects had SARS-CoV-2-specific MBC responses 12 months after infection. The SARS-CoV-2 antibody levels correlated with the MBC frequency at 12 months. Conclusions: The low concentration of SARS-CoV-2 spike protein antibodies indicates that re-exposure to the virus or vaccination are required to use the B-cell immunity to full capacity. The existence of a robust SARS-CoV-2 MBC response at 12 months in most subjects and the substantially increasing antibody half-life provide evidence that the immune response is developing into long-term immunity. The early antibody reaction and the ensuing MBC response are interdependent. Abstract : During the first year after infection the half-life of SARS-CoV-2 spike antibodies increased from 3 months to 2 years. Most infected individuals had robust virus-specific memory B-cell responses 12 months after infection.